Internationalization agency cost corporate governance and capital structure from manufacturing firm listed on indonesia stock exchange - Rezza Vitriya; Uswatun Khasanah (Trigin Publisher, 2023)
Multinational companies have an advantage in raising capital as they often have opportunities to raise capital from other countries. Additionally, companies with more agency conflicts have higher agency costs. Companies with high agency costs tend to use leverage to minimize them. Moreover, the agency conflict is also closely related to the role of good corporate governance in a company. This study has a purpose to determine the impact of the degree of internationalization, agency costs, corporate governance, and control variables against the capital structure of manufacturing firms listed on the Indonesian Stock Exchange. The data type for this study is panel data. The analytical model used is multiple regression analysis. Based on the research results, it can be concluded that agency costs and corporate governance already have a significant impact on the capital structure of Indonesian manufacturing companies in 2019-2021.